2001
DOI: 10.1021/jf010038a
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of Plant Lignans:  New Precursors of Mammalian Lignans Enterolactone and Enterodiol

Abstract: The metabolism of the plant lignans matairesinol, secoisolariciresinol, pinoresinol, syringaresinol, arctigenin, 7-hydroxymatairesinol, isolariciresinol, and lariciresinol by human fecal microflora was investigated to study their properties as mammalian lignan precursors. The quantitative analyses of lignan precursors and the mammalian lignans enterolactone and enterodiol were performed by HPLC with coulometric electrode array detector. The metabolic products, including mammalian lignans, were characterized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
341
5
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 449 publications
(359 citation statements)
references
References 27 publications
8
341
5
5
Order By: Relevance
“…The previous European estimates of lignan intakes do not differ significantly from the lignan intake estimates in the U.S. (Table 2). However, recent reports on the presence of new plant lignan precursors for mammalian lignan production in foods, have changed the view of lignan intake estimates (Heinonen et al, 2001;Milder et al, 2005b). Food composition analyses of lariciresinol (LARI) and pinoresinol (PINO) demonstrated that in many food items these lignans are dominating and may contribute to about 75% of the total lignan intake (Milder et al, 2005a).…”
Section: Intmentioning
confidence: 99%
“…The previous European estimates of lignan intakes do not differ significantly from the lignan intake estimates in the U.S. (Table 2). However, recent reports on the presence of new plant lignan precursors for mammalian lignan production in foods, have changed the view of lignan intake estimates (Heinonen et al, 2001;Milder et al, 2005b). Food composition analyses of lariciresinol (LARI) and pinoresinol (PINO) demonstrated that in many food items these lignans are dominating and may contribute to about 75% of the total lignan intake (Milder et al, 2005a).…”
Section: Intmentioning
confidence: 99%
“…Potential cancer prevention by dietary lignan glycoside, i.e., secoisolariciresinol 37 diglucoside (SDG), has been suggested to be mediated through its metabolites, enterolactone and 38 enterodiol [1][2][3][4][5]. The chemical structures of SDG and its mammalian metabolite enterolactone 39 are shown in Figure 1.…”
Section: Introduction 36mentioning
confidence: 99%
“…The mammalian intestinal micro flora converts plant lignans into enterolignans, mainly enterolactone (ENL) (Heinonen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%